Historia de las ideas filosóficas: un método del filosofar latinoamericano (2021)
This article presents, after some initial considerations on Latin American philosophical thought, the main characteristics and foundations of the history of Latin American philosophical ideas as a suitable framework for thinking about our own problems. Regarding this philosophical discipline, its justification and its validity, some criticisms made to this tradition of thought from postmodern and contemporary philosophy are presented, which have been brought to our attention by some Colombian thinkers. It concludes with the consideration of this historiography as an "our American" philosophical method.